Improving the identification of dementia with Lewy bodies in the context of an Alzheimer’s-type dementia - Alan J. Thomas; Fariba Mahin-Babaei; Mohammad Saidi; Debbie Lett; John Paul Taylor; Lauren Walker; Johannes Attems (Alzheimer’s Research & Therapy, 2018)
Abstract Background Dementia due to Alzheimer’s disease (AD) and dementia with Lewy bodies (DLB) are the two most common neurodegenerative causes of dementia. They commonly occur together, especially in older people, but clinical identification of these diseases in dementia is difficult in such circumstances. We therefore conducted a study using cases with both comprehensive prospective clinical assessments and complete neuropathological examination to determine if it is possible to identify such mixed cases clinically and to determine features which may identify DLB in the presence of AD dementia. Methods At Newcastle Brain Bank we identified subjects who had a clinical diagnosis of dementia and who also had autopsy diagnoses of pure AD, pure DLB, or mixed AD+DLB. All subjects had undergone prospective longitudinal clinical assessments. Mixed AD+DLB patients met neuropathological criteria for both DLB (limbic/neocortical Lewy body disease) and AD (Braak stage V/VI and CERAD B/C). The records of these subjects were carefully reviewed by two specialists in old-age psychiatry blind to autopsy findings to determine baseline and final clinical diagnoses based on these detailed records. The presence of characteristic Lewy body symptoms and other clinical information was also recorded. Results Of 59 subjects included, 19 were AD, 18 DLB, and 22 mixed AD+DLB. At baseline no subjects were correctly identified as having mixed AD+DLB and by final diagnosis only 23% were identified. The only symptom which helped in identifying the presence of Lewy body disease in the context of a mixed AD+DLB dementia was complex visual hallucinations. Conclusions Whilst the identification of DLB in the context of a dementia with an AD pattern is difficult, the emergence of complex visual hallucinations in the context of such a degenerative dementia suggests the presence of Lewy body disease and should encourage a careful assessment. Biomarkers appear likely to be necessary to help improve identification of different disease subtypes underlying dementia.